Large-scale transcriptomic analysis of coding and non-coding pathological biomarkers, associated with the tumor immune microenvironment of thyroid cancer and potential target therapy exploration - Shih, Ming-Lang; Lawal, Bashir; Cheng, Sheng-Yao; Olugbodi, Janet O.; Babalghith, Ahmad O; Ho, Ching-Liang; Cavalu, Simona; Batiha, Gaber El-Saber; Albogami, Sarah; Alotaibi, Saqer S.; Lee, Jih-Chin; Wu, Alexander T. H. (Frontiers in Cell and Developmental Biology, 2022)
Thyroid carcinoma (THCA) is the most prevalent cancer of the endocrine system having a steady increase in global incidence. The pathogenesis of THCA is poorly understood, and the current diagnostic protocols are deficient. Thus identifying novel prognostic biomarkers to improve our understanding of the mechanisms of pathogenesis, diagnosis, and designing therapeutic strategies for THCA is crucial. Herein we integrated differential expressed genes (DEGs) from twenty-seven THCA transcriptomic datasets and identified graded levels of biomarker signature for THCA pathogenesis collectively known as the thyroid tumor-enriched proteins (TTEPs). The TTEPs are clinically associated with tumor stages, poor surgical outcomes, distant metastasis, and worse prognosis. In addition, TTEPs demonstrated a significant association with the T-Cell exclusion in the immune-invasive phenotypes of THCA; the TTEPs were significantly linked to EMT induction, cell-matrix remodeling, and transcriptional dysregulation in THCA. Furthermore, our integrations of microRNAs datasets identified miR-146b-5p and miR-21-5p as THCA specific oncomiRs that modulate the immune response, EMT, migration, cellular proliferation, and stemness. In connection, these oncomiRs and TTEPs concertedly contribute to the molecular mechanisms in THCA. Furthermore, we identified a synthetic compound (Clopidogrel) and a peptide (ocriplasmin) as the most probable ligand inhibitors of the TTEPs. However, our molecular docking study revealed that antrocinnamomin, antcin and antrocin, the bioactive compounds from one of the most reputable Taiwan indigenous medicinal plant (Antrodia camphorata) exhibited higher binding affinities (–5.50 –7.50 Kcal/mol) for the receptors than ligand-affinities demonstrated by the synthetic compound and peptide. Antcin exhibited higher affinities for all the receptors, while antrocin demonstrated the least. Among the targets, fibronectin (FN1) demonstrated high ligandability potential for the compounds while NRCAM demonstrated the least. Collectively, our study identified the potential coding and non-coding theranostic biomarkers that underlay THCA progression, and served as a foundation for subsequent experimental validation and precision medicine approaches in managing THCA.